Inter-rater agreement in the scoring of abstracts submitted to a primary care research conference - Evans Philip H; Graham Anna; Montgomery Alan A; Fahey Tom (BMC, 2002)
Abstract Background Checklists for peer review aim to guide referees when assessing the quality of papers, but little evidence exists on the extent to which referees agree when evaluating the same paper. The aim of this study was to investigate agreement on dimensions of a checklist between two referees when evaluating abstracts submitted for a primary care conference. Methods Anonymised abstracts were scored using a structured assessment comprising seven categories. Between one (poor) and four (excellent) marks were awarded for each category, giving a maximum possible score of 28 marks. Every abstract was assessed independently by two referees and agreement measured using intraclass correlation coefficients. Mean total scores of abstracts accepted and rejected for the meeting were compared using an unpaired t test. Results Of 52 abstracts, agreement between reviewers was greater for three components relating to study design (adjusted intraclass correlation coefficients 0.40 to 0.45) compared to four components relating to more subjective elements such as the importance of the study and likelihood of provoking discussion (0.01 to 0.25). Mean score for accepted abstracts was significantly greater than those that were rejected (17.4 versus 14.6, 95% CI for difference 1.3 to 4.1, p = 0.0003). Conclusions The findings suggest that inclusion of subjective components in a review checklist may result in greater disagreement between reviewers. However in terms of overall quality scores, abstracts accepted for the meeting were rated significantly higher than those that were rejected.